1996
DOI: 10.2307/249477
|View full text |Cite
|
Sign up to set email alerts
|

Information Privacy: Measuring Individuals' Concerns about Organizational Practices

Abstract: Information privacy has been called one of the most important ethical issues of the informal Allen Lee was the accepting senior for this paper. tion age. Public opinion polls show rising levels of concern about privacy among Americans. Against this backdrop, research into issues associated with information privacy is increasing. Based on a number of preliminary studies, it has become apparent that organizational practices, individuals' perceptions of these practices, and societal responses are inextricably lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,528
6
26

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,691 publications
(1,587 citation statements)
references
References 47 publications
27
1,528
6
26
Order By: Relevance
“…For instance an improper access and secondary use of data, the two of four dimensions defined by CFIP [47]. Similarly, our findings relate to the factors identified by IUIPC: collection (interrogation and insecurity) and control (exposure, distortion) [32].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For instance an improper access and secondary use of data, the two of four dimensions defined by CFIP [47]. Similarly, our findings relate to the factors identified by IUIPC: collection (interrogation and insecurity) and control (exposure, distortion) [32].…”
Section: Discussionsupporting
confidence: 74%
“…Such measuring scales are constructed in various ways, for example by asking people directly about their concerns, treating concerns as latent variables or as moderators [38]. For instance, Smith et al [47] developed Concerns for Information Privacy (CFIP) scale aiming to explore the concerns' structure. The study identified four dimensions of privacy concerns: improper access, unauthorized secondary use, error, and collection.…”
Section: Introductionmentioning
confidence: 99%
“…Early research on privacy tended to simply describe privacy as a matter of giving users control over their data (Miller, 1971;Culnan, 1993;Smith et al, 1996). However, more recent research has challenged this and shown how individual-level control over information can mediate privacy concerns, even if access to the data remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [42] had developed and validated an instrument that identified and measured the primary dimensions of individual's concerns about organization information privacy practices. The instrument consists of 15 items that reflects four factors of information privacy ie.…”
Section: ) Information Privacymentioning
confidence: 99%